Screening tools for detecting problematic opioid use and potential application to community pharmacy practice: a review - Lindley B; Cox N; Cochran G (Dove Medical Press, 2019)
Bryn Lindley,1 Nicholas Cox,2 Gerald Cochran31University of Utah, College of Pharmacy, Salt Lake City, UT, USA; 2University of Utah, College of Pharmacy, Department of Pharmacotherapy, Salt Lake City, UT, USA; 3University of Utah, School of Medicine, Division of Epidemiology, Salt Lake City, UT, USAAbstract: Problematic opioid use, constituted by a myriad of conditions ranging from misuse to use disorders, has continued to receive an increasing amount of attention in recent years resulting from the high use of opioids in the United States coinciding with morbidity and mortality. Deaths from drug overdoses increased by over 11% between 2014 and 2015, which supports the need for identification of problematic opioid use in additional health care settings. One of these settings is community pharmacy. The community pharmacy is a unique health service setting to identify and potentially intervene with patients at risk of or exhibit problematic opioid use. Problematic opioid use can be identified using one of the various screening tools in conjunction with evaluating prescription drug monitoring systems. A total of 12 tools were identified that could be employed in community pharmacy settings for identifying problematic opioid use. This review highlights these tools and strategies for use that can be utilized in the community pharmacy, which should be adapted to individual pharmacy settings and local needs. Future research should assess pharmacy personnel’s knowledge and perceptions of problematic opioid use and associated screening tools and interventions, which tools can be most effectively used in a community pharmacy, workflow needs to implement problematic opioid use screenings, and the impact of pharmacist engagement in problematic opioid use screening on patient clinical outcomes.Keywords: opioid use, opioid use disorder, screening tool, community pharmacy